2022
DOI: 10.1080/10717544.2022.2067601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antifungal efficacy of itraconazole loaded aspasomal cream: comparative clinical study

Abstract: Topical conveyance of antifungal agents like itraconazole ITZ has been giving good grounds for expecting felicitous antifungal medicines. The defiance of topical delivery of this poorly water soluble and high-molecular-weight drug, however, mightily entail an adequate vehiculation. ITZ aspasomes, newer antioxidant generation of liposomes, have been designed and enclosed in a cream to ameliorate skin deposition. The proposed creams containing non-formulated ITZ or encapsulated in aspasomes (0.1% or 0.5%) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Aspasomes are the newer antioxidant generation of liposomes; they are nano-vesicular antioxidant systems containing ascorbyl palmitate (a liposoluble vitamin C derivative), cholesterol, and phospholipids that have the ability to form stable vesicular bilayers [157]. The preparation, characterization, and applications of aspasomes were firstly reported in 2004 by Gopinath et al [158].…”
Section: Aspasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspasomes are the newer antioxidant generation of liposomes; they are nano-vesicular antioxidant systems containing ascorbyl palmitate (a liposoluble vitamin C derivative), cholesterol, and phospholipids that have the ability to form stable vesicular bilayers [157]. The preparation, characterization, and applications of aspasomes were firstly reported in 2004 by Gopinath et al [158].…”
Section: Aspasomesmentioning
confidence: 99%
“…The preparation, characterization, and applications of aspasomes were firstly reported in 2004 by Gopinath et al [158]. Since then, aspasomes have been successfully used as nanocarriers for the dermal and transdermal delivery of various drugs and/or bioactives for the treatment of skin injuries (e.g., acne, melasma, psoriasis, fungal infections, skin cancer) [157,[159][160][161][162], or for the management of rheumatoid disease [163] and muscle spasms [164]. Hatem et al developed aspasomes loaded with melatonin, a bioactive antioxidant molecule, as a novel cosmeceutical for the clinical treatment of androgenic alopecia [165].…”
Section: Aspasomesmentioning
confidence: 99%
“…156 Recently, it has been shown that itraconazole-loaded aspasomal cream has a higher efficacy in the treatment of tinea versicolor than non-formulated itraconazole cream alone. 177 Terbinafine Terbinafine, an allylamine antifungal, works by inhibiting squalene epoxidase, thereby blocking the biosynthesis of ergosterol. 87,163,178 The accumulation of squalene accounts for its fungicidal activity whilst ergosterol deficiency accounts for its fungistatic activity.…”
Section: Topical Antifungalsmentioning
confidence: 99%
“… 156 Recently, it has been shown that itraconazole-loaded aspasomal cream has a higher efficacy in the treatment of tinea versicolor than non-formulated itraconazole cream alone. 177 …”
Section: Reviewmentioning
confidence: 99%
“…Oral preparations of ITZ including solutions and capsules as well as intravenous preparations are well-known and widely used in medicine. Recently, due to toxicity concerns associated with systemic use, ITZ is increasingly being investigated for its topical antifungal activities and many reports proved it can be successfully delivered via this route [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%